Gauging the management’s role in the implementation of literature programme - Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2018)
The implementation of literature programme in primary schools since 2003, as an intensive reading programme is to inculcate better reading habits that in turn, will contribute to improve English language proficiency. This study determines the management’s role in the implementation of literature programme in schools via the provision of five elements; support, resources, training, and time allocation. A cross-sectional survey was conducted to identify the five elements provided by the schools’ management. A total number of 234 respondents from 78 schools indicated that majority of respondents were unanimously agreed on the provision of support, resources, training, and time allocation by the schools’ management in the implementation of the programme. This study highlights the impact of management’s role towards the implementation of literature programme, resources for children’s literature, and motivation among teachers towards the implementation of the programme.